Blood compatibility of magnesium and its alloys. (1st October 2015) - Feyerabend, Frank; Wendel, Hans-Peter; Mihailova, Boriana; Heidrich, Stefanie; Agha, Nezha Ahmad; Bismayer, Ulrich; Willumeit-Römer, Regine
Graphical abstract: Abstract: Rationale: Blood compatibility analysis in the field of biomaterials is a highly controversial topic. Especially for degradable materials like magnesium and its alloys no established test methods are available. Objective: The purpose of this study was to apply advanced test methodology for the analysis of degrading materials to get a mechanistic insight into the corrosion process in contact with human blood and plasma. Methods and results: Pure magnesium and two magnesium alloys were analysed in a modified Chandler-Loop setup. Standard clinical parameters were determined, and a thorough analysis of the resulting implant surface chemistry was performed. The contact of the materials to blood evoked an accelerated inflammatory and cell-induced osteoconductive reaction. Corrosion products formed indicate a more realistic, in vivo like situation. Conclusions: The active regulation of corrosion mechanisms of magnesium alloys by different cell types should be more in the focus of research to bridge the gap between in vitro and in vivo observations and to understand the mechanism of action. This in turn could lead to a better acceptance of these materials for implant applications. Statement of Significance: The presented study deals with the first mechanistic insights during whole human blood contact and its influence on a degrading magnesium-based biomaterial. The combination of clinical parameters and corrosion layer analysis has been performed for the first time. It could be of interest due to the intended use of magnesium-based stents and for orthopaedic applications for clinical applications. An interest for the readers of Acta Biomaterialia may be given, as one of the first clinically approved magnesium-based devices is a wound-closure device, which is in direct contact with blood. Moreover, for orthopaedic applications also blood contact is of high interest. Although this is not the focus of the manuscript, it could help to rise awareness for potential future applications.